TEACHING PRACTICE PROGRAM: EFL PRESERVICE TEACHERS’ VOICE - Rudyansah Galang Rahadi (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
ABSTRACT: Teaching is the main task of the teachers. Therefore, to prepare the students in Teaching they must be trained before they deal with the real situations in the school. Teaching practice program is one of the courses that must be completed by students who majored in education so that when they get involved in the world of work they have experience in teaching.This research entitled “Teaching Practice Program : Pre-service teachers’ voice” aims at (1) Pre –service teacher’s perception towards teaching practice 2) finding out problems Pre –service teachers faced in teaching practice. The partisipants of this research involves 30 EFL students as Pre-service teachers, in the Faculty of Teacher Training and Education, Universitas Islam Malang who have completed their teaching practice program which lasted for about 2 months.This research used a descriptive qualitative approach.  The participants of this research were the sixth semester students of teaching practice program in English Education Department Faculty of Teacher Training and Education University of Islam Malang. In gathering the data, the researcher used instruments namely questionnaire and online interview. The questionnaire and online interview was used to answer the research problems.Based on the results of data analysis, the researcher found that pre-service teachers have perceptions that teaching practice helps them in their teaching, especially in the personal competence, the pedagogical competence, the professional competence and the social competence.  Then, the results also showed that the problems that the Pre-service teachers found during teaching practice program were they felt unconfident since they first faced students in classroom. It makes them difficult to adapt the classroom condition. Lack of learning media in teaching such as LCD, projectors, licensing which is difficult in using the lab causes, not mastering the material, will be given to his students cause less effective learning in the classroom.  Pre-service teacher also have problems in their social relationships, especially with students and teachers.  Keywords: Perception, Teaching Practice Program, Pre-service teachers, 4 teacher’s competencies.